Laura's Post-Traumatic Stress Disorder in Ruth Wares' The Woman in Cabin 10 - Angelina Merici Mbambut; Ambar Andayani (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
This study will examine four issues: Laura's PTSD symptoms, PTSD causes, PTSD effects, and the defense mechanisms Laura employs to manage her PTSD. This study uses a literary psychology approach with PTSD concept theory by Rogers & Liness of the National Institute of Mental Health and and defense mechanism theory which will focus on how Laura defends herself in dealing with PTSD. This study uses a qualitative research method. The source of the data is Ruth Wares’ The Woman in Cabin 10. The writer uses data collection techniques by reading the whole novel, identifying, collecting, classifying and analyzing data. Based on the analysis, Laura experiences four symptoms: re-experiencing, avoidance, arousal and reactivity, and cognition and mood. Laura has PTSD due to a break-in at her flat that left serious scars on her face after a burglar tried to lock her in a room and she spent two hours trying to escape and call for help. These events affect aggression, panic attacks, insomnia, claustrophobia, hallucinations, illusions, and horrific imaginations. Laura uses Defense Mechanism as a self-esteem boost to protect herself from disturbing feelings and thoughts that she cannot handle. From the data, Laura uses several defense mechanisms such as repression, denial, rationalization, sublimation, projection, reaction formation, and displacement. Repression and rationalization are the defense mechanisms that Laura uses the most. Laura uses repression to put her anxiety due to PTSD into her subconscious and forget about it so that it does not interfere with her daily life. Laura uses rationalizations to justify her feelings and actions to attain comfort and ego satisfaction.